Efektivitas Program Pertukaran Mahasiswa Merdeka dalam Pengembangan Rasa Percaya Diri Mahasiswa Pendidikan Fisika - Sulastri, Astin; Werdhiana, I Komang; Darmadi, I Wayan; Zaky, Muhammad; Ashad, Ashad (UIN Alauddin Makassar, 2026)
This study aims to determine the effectiveness of the Indonesian Student Exchange Program (PMM) in enhancing the self-confidence of Physics Education students at Tadulako University and to identify the challenges faced during their participation in the program. This research employs a descriptive qualitative method with participants consisting of Physics Education students who have taken part in PMM. Data were collected through questionnaires and in-depth interviews. The questionnaire, consisting of 18 items, showed that the majority of respondents gave positive assessments regarding their self-confidence improvement after participating in PMM, with an overall average score of 89.73%, indicating a very effective category. The interview analysis supports these findings, informants reported an increase in public speaking confidence, adaptability in new environments, and expansion of social networks. Challenges encountered included cross-cultural communication barriers and differences in learning systems, which were managed through effective adaptation strategies. Overall, PMM provided new insights and fostered students’ academic and social self development.